WILDLIFE MANAGEMENT PROSPECTS IN LATIN AMERICA - Dourojeanni, Marc J. (2022)
Wildlife management as an applied science is new in Latin America. Although there were some previous pioneering cases, as in the case of guano birds in Peru, most programs and projects were initiated only in the 1960s and especially in the 1970s, when specialized academic training also began. Currently, there are wildlife management operations in all countries of the region. However, the vast majority of them have conservation purposes, i.e. they are carried out to recover populations of rare or endangered species and/or to stimulate tourism. They are not done to stimulate economic and social development through the production of meat and other products that can be marketed, although in some cases this may occur. One of the few exceptions is the already widespread management of Amazonian River turtles, which serves to improve the food supply of riverine populations. Another is sport hunting, which is still tolerated in a few countries, such as Argentina. The main obstacle to the application of conventional wildlife management is the distorted environmental information that society receives and its consequent strong opposition to hunting, which it considers inhumane and dangerous for the species. On the other hand, influenced by the society´s attitude, wildlife policies and laws are deficient and inefficient, and illegal hunting and wildlife trafficking are widespread. The future of wildlife management for direct economic purposes in the region does not look favorable. Its greatest possibilities are found mainly in portions of natural ecosystems that are not very inhabited, especially tropical forests, for the benefit of indigenous and rural populations, where hunting for sustenance is currently practiced in an unregulated manner.